Covid-19: A Dynamic Analysis of Fatality Risk in Italy - Iosa, Marco; Paolucci, Stefano; Morone, Giovanni (Frontiers in Medicine, 2020)
Italy was the second country in the world that needed to face a wide epidemic of Covid-19 after China. The ratio of the number of fatalities to the number of cases (case fatality ratio, CFR) recorded in Italy was surprisingly high and increased in the month of March. The older mean age of population, the changes in testing policy and the methodological computation of CFR were previously reported as possible explanations for the incremental trend of CFR, a parameter theoretically expected to be constant. In this brief report the official data provided by the Italian Ministry of Health were analyzed using fitting models and the linear fit method approach. This last methodology allowed to reach two findings. The trend of the number of deaths followed with 1-3 days of delay that of positive cases. This delay was not compatible with a biological course of Covid-19, but more with a health management explanation. The second finding is that the Italian number of deaths was not linearly increased with the number of positive cases, but their relationship could modelled by a 2nd order polynomial function. The high number of positive cases might have a direct and an indirect effect on the number of deaths, the latter related to overwhelmed bed capacity of intensive care units.